2021
DOI: 10.1109/access.2021.3050296
|View full text |Cite
|
Sign up to set email alerts
|

Weed Identification Using Deep Learning and Image Processing in Vegetable Plantation

Abstract: Weed identification in vegetable plantation is more challenging than crop weed identification due to their random plant spacing. So far, little work has been found on identifying weeds in vegetable plantation. Traditional methods of crop weed identification used to be mainly focused on identifying weed directly; however, there is a large variation in weed species. This paper proposes a new method in a contrary way, which combines deep learning and image processing technology. Firstly, a trained CenterNet model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
70
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 141 publications
(73 citation statements)
references
References 26 publications
2
70
0
1
Order By: Relevance
“…However, a small proportion of ground objects that are not classified as tea in the ground multispectral images can affect the final quality of the parameter monitoring results. In order to reduce the influence of soil and shadow noise and improve the accuracy of the final quality parameter monitoring results, this study used the EXG index to effectively distinguish the background of green vegetation and soil for image enhancement [31,[79][80][81][82]. The Ostu method was used for image segmentation [32,[83][84][85][86] to enable the effective extraction of the tea areas from the original image that contains other features.…”
Section: Ground Multispectral Imagesmentioning
confidence: 99%
“…However, a small proportion of ground objects that are not classified as tea in the ground multispectral images can affect the final quality of the parameter monitoring results. In order to reduce the influence of soil and shadow noise and improve the accuracy of the final quality parameter monitoring results, this study used the EXG index to effectively distinguish the background of green vegetation and soil for image enhancement [31,[79][80][81][82]. The Ostu method was used for image segmentation [32,[83][84][85][86] to enable the effective extraction of the tea areas from the original image that contains other features.…”
Section: Ground Multispectral Imagesmentioning
confidence: 99%
“…On-the-ground or remote sensing technologies can be used to capture weed images or non-imaging data. Previous research has shown that ground-based approaches (also known as proximal sensing) can capture high-resolution images, allowing for the early detection of substantially lower weed densities, and the discrimination of primary plant species [16,17]. Alternatively, traditional remote sensing platforms such as piloted airborne and satellite may investigate wider areas but have lower image spatial resolution [18].…”
Section: Introductionmentioning
confidence: 99%
“…Vegetables are rich in nutrients, such as vitamins, minerals, and dietary fiber, which are essential for the human body. They are important food sources and economic crops all around the world [1,2]. Plug seedling cultivation and transplantation are important procedures for vegetable production.…”
Section: Introductionmentioning
confidence: 99%